TonB Energy Transduction Systems of Riemerella anatipestifer Are Required for Iron and Hemin Utilization. - HeBin Liao (PLoS ONE, 2015)
Riemerella anatipestifer (R. anatipestifer) is one of the most important pathogens in ducks. The bacteria causes acute or chronic septicemia characterized by fibrinous pericarditis and meningitis. The R. anatipestifer genome encodes multiple iron/hemin-uptake systems that facilitate adaptation to iron-limited host environments. These systems include several TonB-dependent transporters and three TonB proteins responsible for energy transduction. These three tonB genes are present in all the R. anatipestifer genomes sequenced so far. Two of these genes are contained within the exbB-exbD-tonB1 and exbB-exbD-exbD-tonB2 operons. The third, tonB3, forms a monocistronic transcription unit. The inability to recover derivatives deleted for this gene suggests its product is essential for R. anatipestifer growth. Here, we show that deletion of tonB1 had no effect on hemin uptake of R. anatipestifer, though disruption of tonB2 strongly decreases hemin uptake, and disruption of both tonB1 and tonB2 abolishes the transport of exogenously added hemin. The ability of R. anatipestifer to grow on iron-depleted medium is decreased by tonB2 but not tonB1 disruption. When expressed in an E. coli model strain, the TonB1 complex, TonB2 complex, and TonB3 protein from R. anatipestifer cannot energize heterologous hemin transporters. Further, only the TonB1 complex can energize a R. anatipestifer hemin transporter when co-expressed in an E. coli model strain.